Factors that Influence to Sustainability of MSME Muffler Industry in Purbalingga Regency - Faizal Kurniawan; Eliada Herwiyanti; Bambang Setyobudi Irianto (Faculty of Economics and Business Universitas Jenderal Soedirman, 2020)
Financial literacy, accounting literacy, and transactional leadership style are needed by the owners for sustainability of their business, especially for MSME sector. The good level of the financing and leadership is the sucess key to maintain the sustainability of the business. Whether financial literacy, accounting literacy, and transactional leadership style can influence the sustainability in muffler industry Purbalingga? This research analyze were performed with a quantitative descriptive method, that is based on the questionnaire and interviews with respondent. The object of this research is MSMEs muffler industry in Purbalingga. The total sample in this research are 76 sample from the population 166 industry spread in 6 subdistrict in Purbalingga. The result of this research indicate that the financial literacy, accounting literacy and transactional leadership style have a positive effect to the sustainability of muffler industry. The good financial literacy tend to be able to make a good business plan and decisions. Having good accounting literacy in the business tend to be able to produce the good financial standart report, the quality of the financial standard report can help the business to get investment and loan. The good implementation leadership style can help the business sustainability.